2013
DOI: 10.1260/2040-2295.4.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Methodologies of Fully Automatic Whole Heart Segmentation: A Review

Abstract: Whole heart segmentation from magnetic resonance imaging or computed tomography is a prerequisite for many clinical applications. Since manual delineation can be tedious and subject to bias, automating such segmentation becomes increasingly popular in the image computing field. However, fully automatic whole heart segmentation is challenging and only limited studies were reported in the literature. This article reviews the existing techniques and analyzes the challenges and methodologies. The techniques are cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 118 publications
(323 reference statements)
0
84
0
Order By: Relevance
“…There is a wide range of multi-atlas based approaches addressing the problem of cardiac segmentation [7]. We have selected to use the segmentation pipeline proposed by Zuluaga et al [10] as it has shown to be robust in the segmentation of different structures within the heart [13,14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a wide range of multi-atlas based approaches addressing the problem of cardiac segmentation [7]. We have selected to use the segmentation pipeline proposed by Zuluaga et al [10] as it has shown to be robust in the segmentation of different structures within the heart [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…While the segmentation of the main chambers of the heart has been widely addressed [7], little work has focused on the extraction of smaller structures such as the PM. Spreeuwers et al [8] were the first to tackle the problem through a 2D region-based approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the LA+PVs segmentation, Dice score [30], Hausdorff distance (HD) [31] and Average Surface Distance (ASD) [30] were used as evaluation metrics. For the SAS, we employed leave-one-patient-out cross-validation (LOO CV) and reported the cross-validated accuracy, sensitivity, specificity, area under the receiver operating characteristic (ROC) curve (AUC), and the Dice score [32]- [34].…”
Section: Experimental Settings and Performance Measurementioning
confidence: 99%
“…Moreover, the vast literature in CMR analysis tools [14] proposes a large set of semi-and fully-automated methods for adult whole-heart segmentation that could be adapted and applied to paediatric CMR images to ease and improve the delineation and extraction of the heart.…”
Section: Introductionmentioning
confidence: 99%